Soil cover and the impact of its colors on Tannat grapes (Research, Society and Development, 2023)
Covering the soil with plastics is a technique widely used in some cultures, creating a microclimate on site to improve product quality. However, each culture has a different effect depending on the climate, location and management. Therefore, the objective of this work was to cover the soil with fabric of different colors in Tannat grapes in order to improve the quality of the fruit and the elaborated wine. The experimental design was completely randomized, where the plants were covered during the maturation period of the grapes, consisting of four treatments and four repetitions: soil cover with non-woven fabric (TNT) in blue, yellow colors and red and the witnesses without coverage. After the harvest, physical analyzes of the grapes and chemical analysis of the must, vinification, and later the chemical analysis of the wine were carried out. The data obtained were submitted to the Tukey test at 5% significance level. According to the results found, can observe that the ground cover with blue TNT provided a greater color shade of the must and a lower pH. The yellow soil cover, in turn, influenced the higher alcohol content of wine. Therefore, the different colors in soil cover can modify the quality of the Tannat grape and wine.